2016
DOI: 10.1111/1751-2980.12432
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high‐dose dual therapy for Helicobacter pylori rescue therapy: A systematic review and meta‐analysis

Abstract: High-dose PPI-amoxicillin dual therapy is comparable to recommended rescue therapies for H. pylori infection. More researches are needed to determine the efficacy of high-dose dual therapy as a first-line therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 49 publications
2
57
0
Order By: Relevance
“…Rates of eradication 4–8 weeks following treatment completion were significantly greater for patients receiving amoxicillin dual therapy (95%) compared with study‐defined sequential therapy (85%) and amoxicillin‐based triple therapy (81%) (p<0.001). These findings were echoed in a meta‐analysis that found that high‐dose amoxicillin dual therapy (amoxicillin of 2 g/day or more and PPI given more than twice/day) was associated with similar efficacy to other salvage treatments including rifabutin‐based triple therapy and bismuth quadruple therapy …”
Section: Qtc‐interval Prolongationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of eradication 4–8 weeks following treatment completion were significantly greater for patients receiving amoxicillin dual therapy (95%) compared with study‐defined sequential therapy (85%) and amoxicillin‐based triple therapy (81%) (p<0.001). These findings were echoed in a meta‐analysis that found that high‐dose amoxicillin dual therapy (amoxicillin of 2 g/day or more and PPI given more than twice/day) was associated with similar efficacy to other salvage treatments including rifabutin‐based triple therapy and bismuth quadruple therapy …”
Section: Qtc‐interval Prolongationmentioning
confidence: 99%
“…These findings were echoed in a meta-analysis that found that high-dose amoxicillin dual therapy (amoxicillin of 2 g/day or more and PPI given more than twice/day) was associated with similar efficacy to other salvage treatments including rifabutin-based triple therapy and bismuth quadruple therapy. 55 Amoxicillin-based triple therapy, consisting of amoxicillin, metronidazole, and a PPI, may also be an option in patients with a prolonged QTc interval, particularly among patients with a low risk for metronidazole resistance. 9 A large metaanalysis of more than 90 trials demonstrated an eradication rate of up to 70% with this regimen when used as first-line treatment, which was significantly lower compared with clarithromycin triple therapy with amoxicillin (70% vs 77%, p<0.002) or clarithromycin triple therapy with metronidazole (66% vs 78%, p=0.0003).…”
Section: Qtc-interval Prolongationmentioning
confidence: 99%
“…While, 45.8% of the sensitive to Furazolidone were males and 54.2% of them were females. (Gao, et al, 2016), Alboraie et al, (2015), found that bismuth-based quadruple therapy is more effective as a first-line therapy than clarithromycin-based triple therapy for eradicating H. pylori in patients with H. pylori-related chronic gastritis. As standard triple therapies currently fail to cure 80% of H. pylori infections in most populations due to an increased antibiotic resistance, especially to clarithromycin (Tongtawee et al, 2015) It may be concluded that Hp is dependent on temporal hypoacidity or an acidity for its primary infection, but acidity to survive for a long time.…”
Section: Resultsmentioning
confidence: 99%
“…Dual combinations of various doses of amoxicillin (500 mg to 1 g, tid or qid) with high-dose PPI (20-40 mg, tid or qid) have been tested in many countries (including Greece) as alternative therapeutic options, and have yielded highly heterogeneous results, with eradication rates ranging between 53.8% and 93.8% [152][153][154]. Accordingly, although current evidence offers scant support, high-dose dual therapy for 14 days may be an option worth considering when multidrug-resistant H. pylori infection is suspected, such as in patients with multiple treatment failures [155].…”
Section: Recommendation Grade: A; Evidence Level: 1c; Agreement Levelmentioning
confidence: 99%